2015
DOI: 10.47338/jns.v4.169
|View full text |Cite
|
Sign up to set email alerts
|

Hernia of Umbilical Cord: Report of Three Unusual Cases

Abstract: Congenital hernia of umbilical cord is a less frequent entity in newborns and occasionally associated with other maladies. Herein, we report three cases of hernia of umbilical cord. First case was associated with in-utero evisceration of entire small bowel through the presumably ruptured hernia of umbilical cord and other two cases had associated patent vitellointestinal duct (PVID). All of the cases were managed successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Pal et al described an HUC case with gut perforation and extracelomic colonic atresia [27]. Mirza et al reported a case series of three HUC cases: one case associated with in utero evisceration of whole small bowel through presumably ruptured HUC and other 2 cases associated with patent vitellointestinal duct [28]. In Patole1 et al [29], most cases had ileal loops (49.42%) as the content of hernial sacs, 36.78% cases had Meckel's diverticulum, and 6.39% had cecum with the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Pal et al described an HUC case with gut perforation and extracelomic colonic atresia [27]. Mirza et al reported a case series of three HUC cases: one case associated with in utero evisceration of whole small bowel through presumably ruptured HUC and other 2 cases associated with patent vitellointestinal duct [28]. In Patole1 et al [29], most cases had ileal loops (49.42%) as the content of hernial sacs, 36.78% cases had Meckel's diverticulum, and 6.39% had cecum with the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Omphalocele minor, on the other hand, is a condition in which a true abdominal wall defect is present. 7,8 If the herniation is caused by the abdominal wall para-umbilical defect, this type of herniation is called Gastroschisis which is mostly in the right-side. Abdominal organs or various segments of the bowel may herniate from this small (mostly less than 4 cm in diameter) abdominal wall defect.…”
Section: Discussionmentioning
confidence: 99%
“…Although recognized as a distinct entity since 1920s, CHUC is often misdiagnosed as a minor omphalocele, resulting in its underreporting [1,2]. The CHUC with contents as patent vitellointestinal duct (PVID) and its remnants or atresia and even perforation of herniated gut has been reported [3,4]. We are reporting one such rare case of this anomaly which presented with rupture of hernia sac and evisceration of small gut with reverse ileal intussusception via PVID.…”
Section: Introductionmentioning
confidence: 99%